THE EFFICIENCY OF MAGNETIC REFRIGERATION AND A COMPARISON WITH COMPRESSOR REFRIGERATION SYSTEMS - Dorin, Botoc; Plesca, Adrian; Avsec, Jurij (Journal of Energy Technology, 2024)
The objective of this paper is to study the magnetic refrigeration process that makes use of solid materials, such as gadolinium silicon compounds, as the refrigerant. This effect was observed many years ago and was used for cooling to low temperatures. Recently, materials are being developed with which sufficient temperature and entropy change are produced which makes them useful for a wide range of refrigeration applications. Magnetic refrigeration is an emerging technology that utilizes this magnetocaloric effect found in a solid state to produce a refrigeration effect.